Efeito da homogeneização na microestrutura e distribuição característica dos contornos de grão e sua influência nas propriedades mecânicas e desempenho em corrosão do aço inoxidável duplex 2205 - Francislaynne Lages Dias (2019)
Duplex stainless steels are a category of high-alloyed steels characterized by a dual phase ferrite and austenite microstructure. The combination of high ductility of austenite and good mechanical and intergranular corrosion resistances of ferrite give to these steels’ high performance. Its processing usually consists of hot rolling, solution annealing, cold rolling, and final annealing. Some works have been reporting the positive influence of solution annealing, grain refinement and grain boundary character distribution on the good properties of these steel classes. In this category, the standard duplex 2205 (22%Cr-5%Ni-3%Mo) is the workhorse of its generation, being applied where high mechanical and corrosion resistance are required. The aim of this work was to obtain ultrafine grain in 2205 duplex stainless steel through cold rolling with 80% thickness reduction and final annealing. Besides that, intends to evaluate the influence of solution annealing on the microstructural and grain boundary character distribution changes, establishing a relationship between them with mechanical behavior and chloride pitting resistance. It could be noticed that, even with solution annealing, ultrafine grain (around 2 µm) was obtained. Ferrite phase maintains deformation texture even after final annealing, being constituted majority by rotated-cube and α-fiber components. There are indicates of oriented nucleation theory on recrystallization mechanism of ferrite grains. Austenite texture develops in a similar way of austenitic stainless steels when submitted to cold rolling and final annealing, being formed mainly by brass, Goss and S components. The solution annealing leads to the development of low angle grain boundaries, CSL sigma 3 on austenite and CSL sigma17b on ferrite that influenced on the highest ductility without significant strength loss, besides a better passive film stability and chloride pitting resistance.